THE PREDICTIVE VALUE OF DIFFERENT MOTOR FEATURES IN PARKINSON'S. Issue 11 (14th October 2015) - Macleod, Angus; Counsell, Carl
Abstract : Background: Other than tremor dominance (TD) or the postural instability-gait disorder phenotype (PIGD), little is known about what baseline motor characteristics influence prognosis in Parkinson's disease (PD). Methods: We analysed data from the PINE study, a prospective, community-based incident cohort of PD in Aberdeen, Scotland, recruited between 2002–09, with long term follow-up. Baseline motor features derived from the UPDRS part 3 scale were assessed as independent predictors of four outcomes: death, dependence (Schwab & England <80), "death or dependence", and progression to Hoehn & Yahr stage 3 (H&Y3) using Cox regression adjusting for age. Results: 198 patients were analysed (median 6.1 years follow-up). In univariable analyses, bradykinesia score, axial score, limb score, axial/limb ratio, dopa-responsive signs, and dopa-non-reponsive signs were significant predictors of all outcomes. In univariable analyses, asymmetry predicted dependency and death or dependency and TD/PIGD only predicted H&Y3. In multivariable analyses bradykinesia and axial/limb ratio were independent predictors of death and death or dependency and axial score and dopa non-responsive symptoms were predictors for dependency and H&Y3. Discussion: Different motor characteristics were independent predictors of different outcomes. However, a variable relating to severity of axial signs was a common theme across three of these outcomes. Thus, at diagnosis, axial motor features appear to be important predictors of prognosis, perhaps stronger than the TD/PIGD classification and deserve further study.